IMPLEMENTASI MODEL MIND MAPPING DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS IV UPT SPF SD INPRES MINASA UPA - Nurfadilah; Jamaluddin Arifin; Sam’un Mukramin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to improve the learning outcomes of fourth-grade students of UPT SPF SD Inpres Minasa Upa Makassar City on the subject of science learning through the Mind Map learning model. This study uses the Classroom Action Research (CAR) method which is implemented in two cycles, each cycle is carried out for four meetings. Each cycle consists of the stages of planning, implementation, observation, and reflection. The subjects of this study were 16 fourth-grade students of UPT SPF SD Inpres Minasa Upa Makassar City. Data collection techniques were observation, tests (evaluation) and documentation analysis. Data were obtained through observation and tests, which were then analyzed descriptively. The results of the study indicate that the application of the Mind Map model can improve student learning outcomes. In the first cycle, the average student score was 69.37 from all students (16 people) with a learning completion rate of 43.75% which reached the learning objective achievement criteria (KKTP). In cycle II, the average score increased to 86.25, and all 16 students successfully achieved learning completion (100%). Based on these results, it can be concluded that the learning outcomes of science and natural sciences in grade IV students at UPT SPF SD Inpres Minasa Upa, Makassar City can be improved through the Mind Map learning model.